Optimization of Vanillin Extraction from Biodegradation of Oil Palm Empty Fruit Bunches by Serpula lacrymans - Azizah, Nurul; Suhartini, Sri; Nurika, Irnia (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2021)
Abstract This research aims to determine the combination of the ethyl acetate solvent volume and the extraction time that resulted in the optimum response of vanillin content and vanillin yield from the degradation of lignocellulose components from oil palm empty fruit bunches (OPEFB). First, OPEFB degraded using Serpula lacrymans to break down lignocellulosic components. The research design used a centralized composite design with two factors, the volume of ethyl acetate solvent (ml) and the extraction time (minutes). The responses of the experiment are vanillin content and vanillin yields. The optimization analysis results showed that the volume of ethyl acetate solvent and extraction time have a quadratic effect on the vanillin content and vanillin yields. The optimal solution was obtained by treatment with ethyl acetate volume 101.1 ml and extraction time 123.5 minutes. The optimal solution prediction results obtained vanillin content 0.014% and vanillin yield 7.302 μg/g with desirability of 92.8%. Validation based on the optimal solution’s prediction brought response vanillin content 0.013% and vanillin yield 6.950 μg/g. The vanillin content and yield validation results differed respectively by 4.081% and 4.826% lower when compared to predictions on the optimal solution.Keywords: ethyl acetate, vanillin content, vanillin yield AbstrakPenelitian ini bertujuan untuk mengetahui kombinasi dari volume pelarut etil asetat dan lama waktu ektraksi yang menghasilkan respon kadar vanillin dan yield vanillin optimum dari hasil degradasi komponen lignoselulosa tandan kosong kelapa sawit. Tandan kosong kelapa sawit terlebih dahulu didegradasi menggunakan jamur pelapuk Serpula lacrymans untuk memecah komponen lignoselulosa. Rancangan penelitian menggunakan rancangan komposit terpusat dengan dua faktor, yaitu volume pelarut etil asetat (ml) dan lama waktu ekstraksi (menit). Respon dari percobaan tersebut adalah kadar vanillin dan yield vanillin. Hasil penelitian untuk analisis optimasi menunjukkan bahwa faktor volume pelarut etil asetat dan lama waktu ekstraksi berpengaruh secara kuadratik terhadap respon kadar vanillin dan yield vanillin. Hasil solusi optimal diperoleh pada perlakuan dengan volume pelarut etil asetat sebesar 101,1 ml dan lama ekstraksi selama 123,5 menit. Hasil prediksi solusi optimal diperoleh kadar vanillin 0,014% dan yield vanillin 7,302 μg/g dengan ketepatan 92,8%. Validasi yang dilakukan berdasarkan pada prediksi solusi optimal diperoleh respon kadar vanillin 0,013% dan yield vanillin 6,950 μg/g. Hasil validasi kadar dan yield vanillin tersebut memiliki perbedaan masing-masing 4,081% dan 4,826% lebih rendah jika dibandingkan dengan prediksi pada solusi optimal.Kata kunci: etil asetat, kadar vanillin, yield vanillin